2015
DOI: 10.1016/j.jpainsymman.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Control Trials in Patients With Advanced Cancer: A Qualitative Study

Abstract: ContextSymptom control research in patients with advanced cancer is not common. This may be the result of a belief that this research is unethical, not practical, or that patients are not interested. However, the experiences of cancer patients who have actually taken part in symptom control research near the end of life have never been detailed.ObjectivesThe objective was to explore the experiences of patients with advanced cancer who had taken part in symptom control trials.MethodsA prospective two-center stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Currently, the majority of symptom control practice is based on either historical anecdote or low-level evidence, and the lack of research is paradoxical to its importance. 29 There is a need for well-designed clinical trials that either support or (as in our trial) refute practice. We have demonstrated that undertaking symptom control trials in patients with cancer is feasible.…”
Section: Discussionmentioning
confidence: 89%
“…Currently, the majority of symptom control practice is based on either historical anecdote or low-level evidence, and the lack of research is paradoxical to its importance. 29 There is a need for well-designed clinical trials that either support or (as in our trial) refute practice. We have demonstrated that undertaking symptom control trials in patients with cancer is feasible.…”
Section: Discussionmentioning
confidence: 89%
“…However, the need for symptom control studies in patients with cancer has been advocated. 26 One of the key challenges in this area is that patients with advanced cancer are complex and the etiology behind their nausea and vomiting is often multifactorial. Common causes include drugs such as opioids, delayed gastric emptying, mechanical bowel obstruction, increased intracranial pressure, vestibular dysfunction, metabolic problems, and cortical effects such as anxiety or depression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study looking at the patient experience of taking part in a clinical trial described that, even in the absence of any improvement in physical symptoms, participant overall well-being was improved after taking part. 12 The authors discussed the personal value patients took from adopting altruistic motives as well as the potential to benefit from the relationship that they build with researchers. This ties with what is known about well-being in those that are terminally ill where themes of self-awareness, the existence of positive and meaningful relationships with others and the capacity for continued meaning are described as central.…”
Section: Interviewing In the Palliative Care Context -Mr Smithmentioning
confidence: 99%